The journal KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMA PADA MATERI BARISAN DAN DERET DITINJAU DARI GAYA KOGNITIF - Fajriyah Rachmatika; Qurotul Ayun, Qurotul Ayun (Universitas Nahdlatul Ulama Pasuruan, 2023)
This research is motivated by the problem of students' mathematical representation abilities in solving problems of arithmetic sequences and series in class XI IPS 4. Students are less able to show geometric patterns in solving problems, do not use mathematical expressionsand are not confident in expressing their arguments. So this study aims to determine the ability of students' mathematical representations in solving problems of arithmetic sequences and series. This research is a type of qualitative descriptive research. Data were collected by interview, documentation and test methods. This study used 2 interview subjects who were representatives of 2 groups. Namely 1 subject in the FD (Field Dependence) group, 1 subject in the FI (Field Independence) group. Interview subjects were randomly selected based on the results from the GEFT test.Keywords: mathematical representation, problem solving, sequences and series